“How the NEP was broken”: Introductions to the books of the five-volume edition as a historiographic phenomenon (on the 100th anniversary of V.P. Danilov) - Mikhail A. Feldman (Крестьяноведение, 2025)
Introductions to the books in the five-volume How the NEP Was Broken, written under the supervision of the outstanding historian V. P. Danilov, represent a special historiographic phenomenon: the availability of five volumes on the history of the NEP does not mean simplicity of understanding. The difficulty in understanding the materials of five plenums of the Central Committee of the CPSU(b) in 1928–1929 is reinforced by the difficulty in understanding the NEP and the extreme difficulty in realizing the possibilities of the NEP economy as the basis for Soviet industrialization. Collecting a huge number of archival materials about five plenums of the Central Committee of the CPSU(b), selecting and systematizing documents and references, preparing thousands of pages for publication were the first steps towards the scientific feat of Danilov and his younger colleagues, while assessing the importance of published materials and defining criteria for efficiency of the social-economic course allowed Danilov to reach a new level of understanding of the New Economic Policy and to conclude about the artificial nature of abandoning it. Danilov’s argument about the far-from-exhausted potential of the NEP and its possibilities for implementing five-year plans proves Danilov’s place among the most prominent Russian historians.